View Synthesis for Advanced 3D Video Systems. (15th February 2009) - Müller, Karsten; Smolic, Aljoscha; Dix, Kristina; Merkle, Philipp; Kauff, Peter; Wiegand, Thomas
Abstract : Interest in 3D video applications and systems is growing rapidly and technology is maturating. It is expected that multiview autostereoscopic displays will play an important role in home user environments, since they support multiuser 3D sensation and motion parallax impression. The tremendous data rate cannot be handled efficiently by representation and coding formats such as MVC or MPEG-C Part 3. Multiview video plus depth (MVD) is a new format that efficiently supports such advanced 3DV systems, but this requires high-quality intermediate view synthesis. For this, a new approach is presented that separates unreliable image regions along depth discontinuities from reliable image regions, which are treated separately and fused to the final interpolated view. In contrast to previous layered approaches, our algorithm uses two boundary layers and one reliable layer, performs image-based 3D warping only, and was generically implemented, that is, does not necessarily rely on 3D graphics support. Furthermore, different hole-filling and filtering methods are added to provide high-quality intermediate views. As a result, high-quality intermediate views for an existing 9-view auto-stereoscopic display as well as other stereo- and multiscopic displays are presented, which prove the suitability of our approach for advanced 3DV systems.